Analisis Faktor Eksternal dan Internal Pada Perbankan Digital di Bursa Efek Indonesia: Studi Kasus Allo Bank - Muhammad, Hemadanda; Soekarno, Subiakto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2024)
The banking industry is one of the fastest growing and most interesting industries in Indonesia. The banking industry contributes significantly to the Indonesian economy. The development of the banking industry cannot be separated from the influence of technology and massive technological adaptation in Indonesia. The banking industry has begun to create new business models and forms, namely digital banks. Digital banks in Indonesia have attracted a lot of attention because of the new technology they bring and the performance of digital bank shares which have increased significantly in 2021. The increase in the price of digital bank shares did not continue into the following year and continued to decline. One of the digital banks that experienced a significant decline in share prices was Allo Bank. Allo Bank experienced a significant decline in shares even though Allo Bank's performance increased significantly. This study will conduct an external analysis study using the PESTEL and Porter's five forces methods to see the macro and industrial conditions of banking in Indonesia and conduct an internal analysis using a risk-based bank rating to see the performance and health of the bank. External analysis shows that the macro and banking industry show positive opportunities for Allo Bank to develop and internal analysis shows that Allo Bank has very good performance among other digital banks.